Interleukin-2 (IL-2) Interacts With IL-2 Receptor Beta (IL-2Rβ): Its Potential to Enhance the Proliferation of CD4+ T Lymphocytes in Flounder (Paralichthys olivaceus) - Zhou, Xiujuan; Xing, Jing; Tang, Xiaoqian; Sheng, Xiuzhen; Chi, Heng; Zhan, Wenbin (Frontiers in Immunology, 2020)
ABSTRACT Interleukin-2 (IL-2) is an important immunomodulatory cytokine that primarily promotes the activation, proliferation, and differentiation of CD4+ T helper subsets and CD4+ T regulatory cells. In our previous studies, IL-2 and IL-2 receptor beta (IL-2Rβ) genes of flounder (Paralichthys olivaceus) were cloned, and IL-2Rβ molecules expressed on both B and T lymphocytes were identified. In the present study, the interaction of flounder IL-2 (fIL-2) with the IL-2 receptor beta (fIL-2Rβ) were investigated. The proportion of CD4+ T lymphocytes and IL-2Rβ+ cells were detected both in vivo and in vitro. Firstly, the binding of recombinant flounder IL-2 protein (rfIL-2) and rfIL-2Rβ were verified by pull-down assay and ELISA. Indirect immunofluorescence assay showed that rfIL-2 enhanced the proliferation of CD4+ and IL-2Rβ+ cells in the gill and spleen. Furthermore, CD4-1+, CD4-2+ T lymphocytes and IL-2Rβ+ cells were significantly upregulated in cultured peripheral blood lymphocytes (PBLs) with addition of rfIL-2, as shown by Flow cytometry (FCM). The related genes was examined by Q-PCR in cultured PBLs with added rfIL-2. The results showed that the IL-2–IL-2R interaction induced upregulated expression of T lymphocyte surface makers, Th1-related cytokines or transcription factors, and critical genes of the IL-2 signaling pathway. In addition, these IL-2–elicited biological functions and immune responses were downregulated by blocked with anti–rfIL-2Rβ and anti–rfIL-2 Abs, showing that IL-2Rβ plays an indispensable role in IL-2 elicited biological function. Our results demonstrated that the interaction between IL-2 and IL-2Rβ showed its potential to enhance the proliferation of CD4+ T lymphocytes in flounder. It is also found in mammals, a Th1-mediated mechanism regulated by this interaction exists in teleost.